UNIT 6.2 Preparation of Soluble Proteins from Escherichia coli. (3rd November 2014) - Wingfield, Paul T.
Abstract : Purification of human IL‐1β is used in this unit as an example of the preparation of a soluble protein from E. coli . Bacteria containing IL‐1β are lysed, and IL‐1 β in the resulting supernatant is purified by anion‐exchange chromatography, salt precipitation, and cation‐exchange chromatography, and then concentrated. Finally, the IL‐1 β protein is applied to a gel‐filtration column to separate it from remaining higher‐ and lower‐molecular‐weight contaminants, the purified protein is stored frozen or is lyophilized. The purification protocol described is typical for a protein that is expressed in fairly high abundance (i.e., >5% total protein) and accumulates in a soluble state. In addition, the purification procedure serves as an example of how to use classical protein purifications methods, which may also be used in conjunction with the affinity‐based methods now more commonly used. © 2014 by John Wiley & Sons, Inc.